Educação financeira e percepção sobre testes de estresse - Braz, Tércio de Matos (2019)
The discussion on stress testing methodology in banking and banking supervision has increased in recent years. While on the one hand it is clear to the regulator the benefit of stress testing by banks to ensure the financial stability of an economy, there is no evidence in the literature as consumers of banking financial products and services realize that these tests add value to the institution financial management. On the other hand, it has no proof how the level of financial education of consumers influences this valuation. This work proposes to study these issues in an empirical way using an experimental approach with a group of treatments and control. It has been identified that by revealing that banks exercise stress testing activities to the treatment group, consumers forego profitability and choose less profitable banks, but perform stress tests. Such behavior indicates that, in the view of consumers, stress tests ensure the institution security, confidence and greater financial stability. It was also found that consumers with higher levels of financial education recognize the importance of stress testing even more. It is concluded that it is desirable to promote public policies by public and private entities in the field of financial education that raise the level of information to consumers to improve financial decisions, maximizing well-being.